2016
DOI: 10.1002/cplu.201500452
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Perdeuterated 1‐Palmitoyl‐2‐oleoyl‐sn‐glycero‐3‐phosphocholine ([D82]POPC) and Characterisation of Its Lipid Bilayer Membrane Structure by Neutron Reflectometry

Abstract: 1‐Palmitoyl‐2‐oleoyl‐sn‐glycero‐3‐phosphocholine (POPC), an unsaturated acyl chain containing lipid, is often the predominant lipid in eukaryotic cell membranes in which it is crucial for the fluidity of membranes under physiological conditions. Commercially available, partially deuterated [D31]1‐palmitoyl‐2‐oleoyl‐sn‐glycero‐3‐phosphocholine ([D31]POPC) does not provide sufficient isotopic contrast for detailed structural studies of multicomponent membranes through neutron techniques. Herein, a relatively str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…1,2-dimyristoyl-sn-glycero-3-phosphocholine (>99%, hDMPC), 1,2-dimyristoyl-d54-sn-glycero-3-phosphocholine (>99%, dDMPC) and cholesterol (h-cholesterol; >98%) were from Avanti Polar Lipids (Alabaster, AL). Tail deuterated 1-palmitoyl, 2-oleoyl-sn-glycero-3-phosphocholine (d67; overall tail deuteration 95%, dPOPC) was provided by the deuteration facility at ANSTO, produced and purified as previously described (Yepuri et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…1,2-dimyristoyl-sn-glycero-3-phosphocholine (>99%, hDMPC), 1,2-dimyristoyl-d54-sn-glycero-3-phosphocholine (>99%, dDMPC) and cholesterol (h-cholesterol; >98%) were from Avanti Polar Lipids (Alabaster, AL). Tail deuterated 1-palmitoyl, 2-oleoyl-sn-glycero-3-phosphocholine (d67; overall tail deuteration 95%, dPOPC) was provided by the deuteration facility at ANSTO, produced and purified as previously described (Yepuri et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Figure 4 shows the NR data collected for the DOPIP3-containing bilayers where, respectively, hPOPC and dPOPC were used. Indeed, it has been extensively demonstrated that selective deuteration of lipids is a very suitable method to vary the contrast between different sample components without affecting their structure [43][44][45][46][47][48][49][50]. In this case the first goal of the data analysis was to investigate the location of PIP3 within the lipid bilayer, i.e.…”
Section: Nr Measurementsmentioning
confidence: 99%
“…This may be due to partialdeuteration effects, preparation conditions for this specic sample, or combinations of both effects. A more perfect bilayer structure can be achieved using fully deuterated POPC, 49 but these molecules are not commercially available yet. We therefore proceeded to study the interaction of this partially deuterated POPC bilayer with our peptide-dendrimer construct.…”
Section: Rsc Advances Papermentioning
confidence: 99%